The influence of Social Media Branding and e-WOM on Customer Loyalty through Customer Experience - Syamsu, Lingga Nur; Ida Bagus, Cempena; Mujanah, Siti (International Conference On Economics Business Management And Accounting (ICOEMA), 2024)
This study aims to fill the existing gap by focusing on the geographical context of Sidoarjo Regency, East Java, specifically on the problem of broken ESAF frames on Honda automatic scooters, as well as exploring the role of dealers in managing crisis management strategies on social media to mitigate the impact on customer loyalty through user experience. loyal to Honda. This research method is quantitative with an explanatory research approach. The number of samples in this study was 100 with respondents uses Honda brand automatic scooters in Sidoarjo Regency. Distribution of questionnaires via google form. The analysis technique used is descriptive and statistical test Smart PLS. The results of these 7 hypotheses show that 6 hypothesis are accepted and 1 hypotheses is rejected. Social media branding and e-WOM significantly affect customer experience, while social media branding and customer experience significantly affect customer loyalty, whereas e-WOM does not significantly affect customer loyalty. Meanwhile, in the indirect effect, social media branding and e-WOM significantly affect customer loyalty through customer experience.